Decoding depositional and diagenetic conditions of the mid-Cenozoic Puesto del Museo Formation, southern Golfo San Jorge Basin, Patagonia, Argentina. (December 2019) - Gómez-Peral, Lucía E.; Raigemborn, M. Sol; Richiano, Sebastián; Arrouy, M. Julia; Odino-Barreto, A. Lorena; Pérez, Leandro M.; Sial, Alcides N.; Ferreyra, Camila
Abstract: This paper describes an integrated field, petrographic and geochemical study of the Puesto del Museo Formation, a poorly known unit that evidences a Cenozoic transgression at the southernmost Golfo San Jorge Basin. The most striking features of the Puesto del Museo Formation is its occurrence as restricted ~20 m-thick-outcrops composed exclusively of friable cross-stratified grainstones. We analyzed the sedimentary facies and facies associations in order to reconstruct the depositional setting. The petrographic characterization allows assessing the composition as a very homogeneous lithological succession dominated by skeletal grainstones. Geochemistry of trace elements (Mn, Sr, Rb, rare earth elements plus yttrium = REY), and stable isotopes (C and O) were used to characterize the grainstones compositionally, and to constrain environmental and climate conditions that controlled its deposition. The diagenetic environmental comprehension helped to the interpretations of the syn- and post-depositional conditions related to the grainstones. Finally, the stratigraphic position of the Puesto del Museo grainstones into the context of the basin is discussed. This succession can be correlated with the Patagonian marine event (i.e., Golfo San Jorge and Austral basins) that took place during the late Oligocene–early Miocene, related to an elevated global sea level controlled by glacio-eustatic conditions. Highlights: Puesto del Museo Fm can represent the southernmost mid-Cenozoic carbonates at the GSJB. These grainstones deposits flooded a rocky shore composed of the Jurassic volcanites. The cementation begun at the seafloor followed by vadose conditions. Trace elements supported by facies analysis reveal shallow open marine environment. Bioclasts and C-isotope may suggest it as part of the Patagoniense transgression.